The study of effective communication in social awareness campaign through HIV/AIDs anti-discrimination & anti-stigmatisation campaigns, and exploring the factors behind effective communication. - Tan, Wen Chuan. (2009)
The 6th Singapore AIDS Conference in November 2008 was the first time Singapore put its focus in the issue surrounding discrimination and stigmatisation towards people living with HIV/AIDS, and this showed that more efforts will be put into the communication of this issue to the public in the future. Singapore has a lot to learn from other countries like Canada, United State and Hong Kong that had already established strong foundation towards this sensitive topic. Therefore, there is a need to establish an effective communication to address the issue of HIV/AIDS discrimination and stigmatisation. This is urgent because for many years our nation has been constantly advocating on the danger of contacting the virus and disease, as such, generating fear towards it. This thesis will look into and analysis HIV/AIDS campaigns done in Singapore and successful HIV/AIDS anti-discrimination campaigns from other countries. And, find out the reason why HIV/AIDS sufferers were discriminated in our society. With the information gathered, appropriate theories in designs will be used to aid the process of creating a HIV/AIDS campaign that will communication the issue of discrimination and stigma in Singapore.